Ti3C2TX MXene/g-C3N4 heterojunction for battery thermal runaway management - Chen, Bin; Gao, Xue-Qin; Deng, Cong (Chemical engineering journal (Lausanne, Switzerland : 1996), 2025)
•A planar strategy is presented in Ti3C2TX/g-C3N4 heterostructures.•The gas max response reaches hydrogen (5 ppm@2.9 %) and mixtures (150 ppm@4.3 %).•The variation of layer spacing and flow rate is validated by molecular dynamics and gas simulation.